Analysis of Various Crosstalk Avoidance Techniques in Optical Multistage Interconnection Networks - Chopra, Shruti (My University, 2009)
The problem undertaken for dissertation is “Analysis of cross avoidance techniques in Optical Multistage Interconnection Networks”. The major problem called crosstalk is caused by coupling of two signals within a switching element. A lot of work has already been done in designing various algorithms and methods so that good quality solution can be obtained. Window method is the method that is used to find the messages that are not in the same group because it causes crosstalk in the network. Then comes Improved window method in which the first window is eliminated for this we make the conflict matrix initialized to 0, here number of windows is M-1, where M=log2N and N is size of network. It takes less time to find conflicts than the windows method. Then comes the most efficient method called Bitwise Window method. In this method, source and destination address is in decimal format. There is only one decimal number in each row and each window for comparison and finding a conflict. Bitwise window method is the best method as its execution time is very less in comparison to other methods. Four Heuristic algorithms are there that are also used to avoid crosstalk. The Bitwise heuristic techniques can improve the time nearly more than 10 times special when the network size is large. All the window methods have been implemented using ’C’ language and results have been analyzed.
Keywords: Optical Multistage Interconnection Networks